Artificial Intelligence – Ethical Issues - Stanisław Ciupka; Oliwia Wieczorek (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej)
The accelerating progress in the field of artificial intelligence (AI) is giving rise to increasingly lively philosophical discussions and new ethical challenges that humanity must face. An inevitable element of this progress is the growing autonomy of artificial intelligence in terms of making decisions that are not directly supervised by humans. Many AI decisions give rise and will give rise to moral conflicts and dilemmas. It is worth considering today what measures are necessary to equip future autonomous, self-learning and self-replicating devices equipped with artificial intelligence, and at the same time capable of acting independently and in a large range of variability of external conditions, with a specific type of ethical intelligence. The problem that both the designers and users of objects equipped wit artificial intelligence must face is the need to optimally balance the reasons, needs and interests between both sides of human- nonhuman interaction. In a situation of growing autonomy of artificial intelligence increasingly does not fit the dominant anthropocentric ethics. It is becoming necessary to expand and modify the model of ethics, which will allow to predict and encompass the so far insufficient area of mutual relations between humans and artificial intelligence.